Effects of ocean warming on weight at age, recruitment, and age diversity for Gulf of Alaska walleye pollock - Michael A. Litzow; Krista B. Oke; Alisa A. Abookire; Benjamin J. Laurel; Franz J. Mueter (Fisheries Research, 2026)

Phytoplankton communities respond to environmental shifts in the eastern Bering Sea: Low abundances of Calanus copepods correlate with larger but potentially adverse phytoplankton taxa during warm stanzas - Jeanette C. Gann; David G. Kimmel; Franz J. Mueter; Michael W. Lomas; Lisa B. Eisner; Sarah L. Mincks (Limnology and Oceanography, 2026)
Phytoplankton communities change in response to environmental conditions, potentially impacting zooplankton through altered trophic interactions. In the Bering Sea, warm and cold stanzas in recent decades correlated with changes in community structure of zooplankton and fish. Attempts to link these trends to primary producers based on patterns in total chlorophyll a (Chl a ) concentration have been unsuccessful. Using Chl a as a proxy for food availability ignores potential consequences of community shifts in phytoplankton, which span a vast range of cell shapes, sizes, and biochemical composition that do not contribute equally to primary consumer diets. We analyzed size structure and taxonomic composition of phytoplankton in relation to environmental variables from 2003 to 2018 and examined relationships to the abundance of two copepod genera ( Calanus and Pseudocalanus ) important to age‐0 pollock diets. Three distinct environmental stanzas were identified: Warm1 (2003–2005) with high temperature and salinity and low nutrient concentrations favoring dominance of flagellates, ciliates, and dinoflagellates, and low abundances of Calanus ; Cold (2006–2012) with low temperature and salinity and high nitrogen concentrations favoring the cryptophyte Rhodomonas and small centric diatoms, and high Calanus abundances; and Warm2 (2014–2018) with high temperature, salinity, and nutrients (including high SiO 4 ), supporting high abundances of elongated rod‐like diatoms, and low abundances of Calanus . Calanus abundance (2003–2018) was significantly negatively correlated with biomass of large (> 10 μm) phytoplankton, with moderate‐strong negative correlations with the taxa Leptocylindrus , Ceratium , and Dictyocha , and strong positive correlations with Rhodomonas , highlighting links between phytoplankton and zooplankton community structure in response to alternating environmental stanzas.

Late summer distribution and abundance of larval snow crab (Chionoecetes opilio) and pelagic crab communities in the U.S. Pacific Arctic Gateway - Jared D. Weems; Franz J. Mueter; Alexei I. Pinchuk; David G. Kimmel (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

DNA metabarcoding reveals surprisingly diverse diet in under-ice polar cod during autumn - Sarah M. Maes; Alexei I. Pinchuk; Franz Mueter; Henrik Christiansen; Bart Hellemans; Ron ten Boer; Filip A. M. Volckaert; Hauke Flores (Polar Biology, 2025)
Polar cod ( Boreogadus saida ) functions as a key species in the Arctic food web and is one of the most abundant Arctic fishes. Despite its ecological importance, the feeding ecology of juveniles sampled under the sea ice is unknown. In November 2019, at the onset of sea ice formation, sea-ice associated polar cod and zooplankton samples were collected in the Beaufort and Chukchi seas. Stomach contents were highly digested and largely unidentifiable by morphological analysis. DNA metabarcoding, however, facilitated identification of most prey items to the species-level. Juvenile polar cod had a broad dietary spectrum and consumed at least 45 taxa, with calanoid copepods and ostracods being the most abundant prey taxa. The most frequent prey species were the pelagic ostracod Boroecia maxima and the calanoid copepods Calanus hyperboreus and Metridia longa . Contrary to expectations, the upper water column in the Alaskan Arctic below consolidated ice contained moderate abundances of energy-rich epipelagic zooplankton and under-ice fauna, particularly calanoid copepods and ice amphipods, in late fall. This zooplankton may provide a critical resource for late hatchers to survive in low-temperature habitats with low energy expenditure.

Atmospheric Pressure Rivalry Between the Arctic and Northern Pacific: Implications for Alaskan Climate Variability - Igor V. Polyakov; Thomas J. Ballinger; James E. Overland; Stephen J. Vavrus; Seth L. Danielson; Rick Lader; Uma S. Bhatt; Amy S. Hendricks; Franz J. Mueter (International Journal of Climatology, 2024)
Located at the confluence of the Arctic and North Pacific and with Alaska at its heart, the Pacific Arctic Region (PAR) is a unique and interconnected regional climate system. Significant climatic changes in the PAR are described by a novel, mobile monthly Alaska Arctic Front (AAF) index, which is defined by sea level pressure differences between the migratory cores of the Beaufort High and Aleutian Low. Regional climate variability associated with the AAF shows prominent decadal signatures that are driven by the opposing effects of the North Pacific and the Arctic atmospheric pressure fields. Low AAF (negative phase) is dominated by North Pacific forcing, whereas high AAF (positive phase) is dominated by Arctic atmospheric processes. The recent (2011–2021) negative AAF phase, which is associated with the westward displacement of Aleutian Low explaining stronger northward winds and enhanced water transport northward through Bering Strait, is conducive to increased oceanic heat and freshwater content, reduced regional sea ice cover in the PAR, and to the expansion of Pacific species into the Arctic. These factors are all indicators of the Pacification of the Arctic Ocean, a key feature of climate change related to progression of anomalous Pacific water masses and biota into the polar basins. It is not yet clear if or when the recent phase of decadal variability will change and alter the rate of Pacification of the Arctic climate system.

Movement and diving behavior of satellite-tagged male sperm whales in the Gulf of Alaska - Lauren A. Wild; Franz J. Mueter; Jan M. Straley; Russ D. Andrews (Frontiers in Marine Science, 2024)
Male sperm whales ( Physeter macrocephalus ) are known to interact with and depredate from commercial longline fishing vessels targeting sablefish ( Anoplopoma fimbria ) in the Gulf of Alaska (GOA). This study aims to better understand their movement patterns and diving behavior in this region, and in relation to depredation behavior. Between 2007 and 2016 a total of 33 satellite tags were deployed on sperm whales interacting with fishing vessels in the eastern GOA. A subset of these tags also collected dive characteristics. We used state space models to interpolate hourly positions from tags and estimate behavioral state from 29 usable tag records, 14 of which had associated dive information. Whales exhibited slower horizontal movement (1.4 km/hr) within GOA waters compared to south of the GOA (5.5 km/hr), indicating tagged whales sped up when they left the region. Behavioral states indicated primarily foraging behavior (82% of locations) in the GOA and primarily transiting behavior (74% of locations) when whales left the GOA. Dive data showed average ( ± Standard Deviation) maximum dive depths of 396 m ( ± 166), and dive durations of 32 min (± 9). Generalized additive models indicated that dives were significantly deeper and longer during the daytime than dawn, dusk, or nighttime, and dives were significantly deeper and shorter during quarter moons, when tidal currents are weakest. Maximum dive depth decreased in areas of higher sablefish CPUE, suggesting a potential link between the sablefish fishery and depredation behavior. As seafloor depth increased, up to 800 m, dives became deeper, indicating that whales were likely targeting both bathypelagic and mesopelagic prey. This highlights the importance of the GOA continental slope as a foraging ground for male sperm whales. This enhanced understanding of sperm whale foraging ecology informs management and conservation efforts in high latitude foraging grounds.

Hypoxia vulnerability in the salmon watersheds of Southeast Alaska - Christopher J. Sergeant; J. Ryan Bellmore; Rebecca A. Bellmore; Jeffrey A. Falke; Franz J. Mueter; Peter A.H. Westley (Science of The Total Environment, 2023)

Arctic cod (Boreogadus saida) hatching season and growth rates in the Bering, Chukchi and Beaufort seas - Zane M. Chapman; Franz J. Mueter; Brenda L. Norcross; Dion S. Oxman (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Environmental Drivers of Nearshore Fish Community Composition and Size Structure in Glacially Influenced Gulf of Alaska Estuaries - Nina C. Lundstrom; Anne H. Beaudreau; Franz J. Mueter; Brenda Konar (Estuaries and Coasts, 2022)
Coastal ecosystems in Alaska are undergoing rapid change due to warming and glacier recession. We used a natural gradient of glacierized to non-glacierized watersheds (0–60% glacier coverage) in two regions along the Gulf of Alaska—Kachemak Bay and Lynn Canal—to evaluate relationships between local environmental conditions and estuarine fish communities. Multivariate analyses of fish community data collected from five sites per region in 2019 showed that region accounted for the most variation in community composition, suggesting that local effects of watershed type were masked by regional-scale variables. Seasonal shifts in community composition were driven largely by the influx of juvenile Pacific salmon ( Oncorhynchus spp.) in late spring. Spatiotemporal differences among fish communities were partly explained by salinity and temperature, which accounted for 19.5% of the variation in community composition. We used a multi-year dataset from Lynn Canal (2014–2019) to examine patterns of mean length for two dominant species. Generalized additive mixed models indicated that Pacific staghorn sculpin ( Leptocottus armatus ) mean length varied along site-specific seasonal gradients, increasing gradually through the summer in the least glacially influenced sites and increasing rapidly to an asymptote of ~ 150 mm in the most glacially influenced sites. Starry flounder ( Platichthys stellatus ) mean length was more strongly related to environmental conditions, increasing with temperature and turbidity. Together, our findings suggest that community compositions of estuarine fishes show greater variation at the regional scale than the watershed scale, but species-specific variation in size distributions may indicate differences in habitat quality across watershed types within regions.

Environmental Filtering Influences Functional Community Assembly of Epibenthic Communities - Lauren Sutton; Franz J. Mueter; Bodil A. Bluhm; Katrin Iken (Frontiers in Marine Science, 2021)
Community assembly theory states that species assemble non-randomly as a result of dispersal limitation, biotic interactions, and environmental filtering. Strong environmental filtering likely leads to local assemblages that are similar in their functional trait composition (high trait convergence) while functional trait composition will be less similar (high trait divergence) under weaker environmental filters. We used two Arctic shelves as case studies to examine the relationship between functional community assembly and environmental filtering using the geographically close but functionally and environmentally dissimilar epibenthic communities on the Chukchi and Beaufort Sea shelves. Environmental drivers were compared to functional trait composition and to trait convergence within each shelf. Functional composition in the Chukchi Sea was more strongly correlated with environmental gradients compared to the Beaufort Sea, as shown by a combination of RLQ and fourth corner analyses and community-weighted mean redundancy analyses. In the Chukchi Sea, epibenthic functional composition, particularly body size, reproductive strategy, and several behavioral traits (i.e., feeding habit, living habit, movement), was most strongly related to gradients in percent mud and temperature while body size and larval development were most strongly related to a depth gradient in the Beaufort Sea. The stronger environmental filter in the Chukchi Sea also supported the hypothesized relationship with higher trait convergence, although this relationship was only evident at one end of the observed environmental gradient. Strong environmental filtering generally provides a challenge for biota and can be a barrier for invading species, a growing concern for the Chukchi Sea shelf communities under warming conditions. Weaker environmental filtering, such as on the Beaufort Sea shelf, generally leads to communities that are more structured by biotic interactions, and possibly representing partitioning of resources among species from intermediate disturbance levels. We provide evidence that environmental filtering can structure functional community composition, providing a baseline of how community function could be affected by stressors such as changes in environmental conditions or increased anthropogenic disturbance.

Marine biodiversity refugia in a climate‐sensitive subarctic shelf - Irene D. Alabia; Jorge García Molinos; Takafumi Hirata; Franz J. Mueter; Toru Hirawake; Sei‐Ichi Saitoh (Global Change Biology, 2021)
The subarctic shelf of the Eastern Bering Sea (EBS) is one of the world's most productive marine environments, exposed to drastic climate changes characterized by extreme fluctuations in temperature, sea ice concentration, timing, and duration. These climatic changes elicit profound responses in species distribution, abundance, and community composition. Here, we examined the patterns of alpha and temporal beta diversity of 159 marine taxa (66 vertebrates and 93 invertebrate species) from 29 years (1990–2018) of species observations from the NOAA bottom trawl surveys in the EBS. Based on these data, we identified geographically distinct refugial zones in the northern and southern regions of the middle shelf, defined by high species richness and similarity in community species composition over time. These refugial zones harbor higher frequencies of occurrence for representative taxa relative to the regions outside of refugia. We also explored the primary environmental factors structuring marine biodiversity distributions, which underpinned the importance of the winter sea ice concentration to alpha and temporal beta diversity. The spatial biodiversity distributions between high and low winter sea ice regimes highlighted contrasting signals. In particular, the latter showed elevated species richness compared to the former. Further, the temporal beta diversity between the high and low winter sea ice periods underpinned an overall increase in the compositional similarity of marine communities in the EBS. Despite these spatiotemporal differences in biodiversity distributions, the identified refugia represent safe havens of marine biodiversity in the EBS. Distinguishing these areas can help facilitate conservation and management efforts under accelerated and ongoing climatic changes.

A Decade of Incorporating Social Sciences in the Integrated Marine Biosphere Research Project (IMBeR): Much Done, Much to Do? - Ingrid van Putten; Rachel Kelly; Rachel D. Cavanagh; Eugene J. Murphy; Annette Breckwoldt; Stephanie Brodie; Christopher Cvitanovic; Mark Dickey-Collas; Lisa Maddison; Jess Melbourne-Thomas; Haritz Arrizabalaga; Kumiko Azetsu-Scott; et al. (Frontiers in Marine Science, 2021)
Successful management and mitigation of marine challenges depends on cooperation and knowledge sharing which often occurs across culturally diverse geographic regions. Global ocean science collaboration is therefore essential for developing global solutions. Building effective global research networks that can enable collaboration also need to ensure inter- and transdisciplinary research approaches to tackle complex marine socio-ecological challenges. To understand the contribution of interdisciplinary global research networks to solving these complex challenges, we use the Integrated Marine Biosphere Research (IMBeR) project as a case study. We investigated the diversity and characteristics of 1,827 scientists from 11 global regions who were attendees at different IMBeR global science engagement opportunities since 2009. We also determined the role of social science engagement in natural science based regional programmes (using key informants) and identified the potential for enhanced collaboration in the future. Event attendees were predominantly from western Europe, North America, and East Asia. But overall, in the global network, there was growing participation by females, students and early career researchers, and social scientists, thus assisting in moving toward interdisciplinarity in IMBeR research. The mainly natural science oriented regional programmes showed mixed success in engaging and collaborating with social scientists. This was mostly attributed to the largely natural science (i.e., biological, physical) goals and agendas of the programmes, and the lack of institutional support and push to initiate connections with social science. Recognising that social science research may not be relevant to all the aims and activities of all regional programmes, all researchers however, recognised the (potential) benefits of interdisciplinarity, which included broadening scientists’ understanding and perspectives, developing connections and interlinkages, and making science more useful. Pathways to achieve progress in regional programmes fell into four groups: specific funding, events to come together, within-programme-reflections, and social science champions. Future research programmes should have a strategic plan to be truly interdisciplinary, engaging natural and social sciences, as well as aiding early career professionals to actively engage in such programmes.

Changes in Diversity and Species Composition Across Multiple Assemblages in the eastern Chukchi Sea During Two Contrasting Years are Consistent with Borealization - Franz Mueter; Katrin Iken; Lee Cooper; Jacqueline Grebmeier; Kathy Kuletz; Russell Hopcroft; Seth Danielson; Eric Collins; Dan Cushing (Oceanography, 2021)
The Arctic Marine Biodiversity Observing Network monitors biological assemblages on taxonomic scales ranging from microbes to seabirds on the northeast Chukchi Sea shelf to improve understanding of their responses to changing environmental conditions, including climate change. Here, we compare two years, 2015 and 2017, the latter characterized by a much larger spatial extent of warmer, more saline Pacific waters within the study region. These environmental differences were associated with changes in the taxonomic diversity and species composition of eight different assemblages. Impacts included decreases in the diversity and abundance of benthic species and increases in the diversity and abundance of zooplankton and demersal fish. These observations are consistent with the expected patterns of borealization, a term that describes changes from polar to more southern or boreal conditions and that have been observed on other Arctic inflow shelves where there is communication with the global ocean. A decoupling of the seabird assemblage from other assemblages in 2017 suggests that seabirds were unable to fully adjust to changing prey conditions in 2017. Pronounced differences in the taxonomic composition and a substantial decline in taxonomic diversity of bacteria and protists in 2017 remain unexplained but suggest that these microbes are highly susceptible to changing conditions. Continued warming of the Chukchi Sea will likely result in further borealization, with differential impacts on pelagic and benthic communities.

Autonomous vehicle surveys indicate that flow reversals retain juvenile fishes in a highly advective high‐latitude ecosystem - Robert M. Levine; Alex De Robertis; Daniel Grünbaum; Rebecca Woodgate; Calvin W. Mordy; Franz Mueter; Edward Cokelet; Noah Lawrence‐Slavas; Heather Tabisola (Limnology and Oceanography, 2021)
Summer surveys of the Chukchi Sea indicate that high densities of age‐0 gadid fishes, historically Arctic cod ( Boreogadus saida ) but recently also walleye pollock ( Gadus chalcogrammus ), dominate the pelagic fish community. Adults are comparatively scarce, suggesting that either overwinter survivorship of age‐0 gadids is low, or that they emigrate to other areas of the Pacific Arctic. To examine population movement, we conducted repeat acoustic surveys with saildrone autonomous surface vehicles equipped with echosounders throughout summer 2018. The saildrones' range and endurance enabled two large‐scale surveys of the U.S. Chukchi shelf. Acoustic backscatter, a proxy for fish density, was highest in regions with sea surface temperatures of 6–8°C, and lowest in areas influenced by recent ice melt. A subarea of the central Chukchi was surveyed a total of four times; backscatter in this subarea increased by > 85% from late‐July to mid‐September. As summer progressed, fish developed more extensive diel vertical migrations and backscatter from individuals doubled. Both changes suggest increases in backscatter were driven primarily by increasing body size. Particle tracking simulations indicated age‐0 gadids were likely retained over the Chukchi shelf by extended periods of wind‐driven southward flow during the survey period before strong northward flow in late fall transported them to the north. These findings suggest that in summer 2018, age‐0 gadids were advected northward to the Chukchi shelf from the northern Bering Sea, where they were retained during a period of growth until late fall before being advected farther north toward the Chukchi and Beaufort shelf breaks.

Social behavior increases in multipod aggregations of southern Alaska resident killer whales ( Orcinus orca ) - Daniel W. Olsen; Craig O. Matkin; Franz J. Mueter; Shannon Atkinson (Marine Mammal Science, 2020)
Killer whales ( Orcinus orca ) are highly social and occasionally gather in large aggregations that reach 150 individuals. During 338 encounters with Southern Alaska resident killer whales, we collected 1,352 hr of behavioral data to assess the probability of various behaviors based on season, number of pods present, presence of rarely sighted pods, and number of mitochondrial DNA haplotypes present. A binomial generalized linear model was used to estimate the role of these factors in the probability of four behaviors, foraging, resting, socializing, and traveling. The presence of “rarely sighted” pods (sighted in

Arctic gadids in a rapidly changing environment - Franz Mueter; Caroline Bouchard; Haakon Hop; Benjamin Laurel; Brenda Norcross (Polar Biology, 2020)

Spatial patterns, environmental correlates, and potential seasonal migration triangle of polar cod (Boreogadus saida) distribution in the Chukchi and Beaufort seas - Caitlin E. Forster; Brenda L. Norcross; Franz J. Mueter; Elizabeth A. Logerwell; Andrew C. Seitz (Polar Biology, 2020)

Ontogenetic changes in the buoyancy and salinity tolerance of eggs and larvae of polar cod (Boreogadus saida) and other gadids - Mara L. Spencer; Cathleen D. Vestfals; Franz J. Mueter; Benjamin J. Laurel (Polar Biology, 2020)

Examination of saffron cod Eleginus gracilis (Tilesius 1810) population genetic structure - Noël A. Smé; Sarah Lyon; Franz Mueter; Vladimir Brykov; Yasunori Sakurai; A. J. Gharrett (Polar Biology, 2020)

Influences of temperature, predators, and competitors on polar cod (Boreogadus saida) at the southern margin of their distribution - Jennifer M. Marsh; Franz J. Mueter (Polar Biology, 2020)

Environmental and biological influences on the distribution and population dynamics of polar cod (Boreogadus saida) in the US Chukchi Sea - Jennifer M. Marsh; Franz J. Mueter; Terrance J. Quinn (Polar Biology, 2020)

Multispecies biomass dynamics models reveal effects of ocean temperature on predation of juvenile pollock in the eastern Bering Sea - Tadayasu Uchiyama; Franz J. Mueter; Gordon H. Kruse (Fisheries Oceanography, 2020)
Walleye pollock ( Gadus chalcogrammus ) supports one of the largest commercial fisheries in the world. Juvenile pollock are important forage fish in the eastern Bering Sea (EBS) ecosystem, often representing the largest fraction in the diets of major Bering Sea piscivores. Large variability in the EBS pollock stock biomass in recent years has been attributed primarily to fluctuations in recruitment. It has been hypothesized that predation rates on forage fishes increase when the cold pool (a body of cold water

Humpback Whale Movements and Behavior in Response to Whale-Watching Vessels in Juneau, AK - Alicia R. Schuler; Sarah Piwetz; Jacopo Di Clemente; David Steckler; Franz Mueter; Heidi C. Pearson (Frontiers in Marine Science, 2019)

Spatio-temporal distribution of polar cod (Boreogadus saida) and saffron cod (Eleginus gracilis) early life stages in the Pacific Arctic - Cathleen D. Vestfals; Franz J. Mueter; Janet T. Duffy-Anderson; Morgan S. Busby; Alex De Robertis (Polar Biology, 2019)

Effects of the North Pacific Current on the productivity of 163 Pacific salmon stocks - Michael J. Malick; Sean P. Cox; Franz J. Mueter; Brigitte Dorner; Randall M. Peterman (Fisheries Oceanography, 2017)
Horizontal ocean transport can influence the dynamics of higher‐trophic‐level species in coastal ecosystems by altering either physical oceanographic conditions or the advection of food resources into coastal areas. In this study, we investigated whether variability in two North Pacific Current (NPC) indices was associated with changes in productivity of North American Pacific salmon stocks. Specifically, we used Bayesian hierarchical models to estimate the effects of the north‐south location of the NPC bifurcation (BI) and the NPC strength, indexed by the North Pacific Gyre Oscillation (NPGO), on the productivity of 163 pink, chum, and sockeye salmon stocks. We found that for salmon stocks located in Washington (WA) and British Columbia (BC), both the BI and NPGO had significant positive effects on productivity, indicating that a northward‐shifted bifurcation and a stronger NPC are associated with increased salmon productivity. For the WA and BC regions, the estimated NPGO effect was over two times larger than the BI effect for pink and chum salmon, whereas for sockeye salmon the BI effect was 2.4 times higher than the NPGO. In contrast to WA and BC stocks, we found weak effects of both horizontal ocean transport processes on the productivity of salmon stocks in Alaska. Our results indicated that horizontal transport pathways might strongly influence population dynamics of Pacific salmon in the southern part of their North American ranges, but not the northern part, suggesting that different environmental pathways may underlie changes in salmon productivity in northern and southern areas for the species under consideration.

The ecology of gadid fishes in the circumpolar Arctic with a special emphasis on the polar cod (Boreogadus saida) - Franz J. Mueter; Jasmine Nahrgang; R. John Nelson; Jørgen Berge (Polar Biology, 2016)

The ecology of gadid fishes in the circumpolar Arctic with a special emphasis on the polar cod (Boreogadus saida) - Franz J. Mueter; Jasmine Nahrgang; R. John Nelson; Jørgen Berge (Polar Biology, 2016)

Effectiveness of single-pass backpack electrofishing to estimate juvenile coho salmon abundance in Alaskan headwater streams - Kevin Foley; Amanda Rosenberger; Franz Mueter (Fisheries Science, 2015)

Evidence of bottom-up limitations in nearshore marine systems based on otolith proxies of fish growth - Vanessa R. von Biela; Gordon H. Kruse; Franz J. Mueter; Bryan A. Black; David C. Douglas; Thomas E. Helser; Christian E. Zimmerman (Marine Biology, 2015)

Chum salmon ( Oncorhynchus keta ) growth and temperature indices as indicators of the year–class strength of age‐1 walleye pollock ( Gadus chalcogrammus ) in the eastern Bering Sea - Ellen M. Yasumiishi; Keith R. Criddle; Nicola Hillgruber; Franz J. Mueter; John H. Helle (Fisheries Oceanography, 2015)
Ecosystem‐based fisheries management requires the development of physical and biological time series that index ocean productivity for stock assessment and recruitment forecasts for commercially important species. As recruitment in marine fish is related to ocean condition, we developed proxies for ocean conditions based on sea surface temperature ( SST ) and biometric measurements of chum salmon ( Oncorhynchus keta ) captured in the walleye pollock ( Gadus chalcogrammus ) fishery in the eastern Bering Sea in three periods (July 16–30, September 1–15 and September 16–30). The main purpose of this paper was to evaluate Pacific salmon ( Oncorhynchus spp.) growth as a possible indicator of ocean conditions that, in turn, may affect age‐1 walleye pollock recruitment. Marine growth rates of Pacific salmon are the result of a complex interplay of physical, biological and population‐based factors that fish experience as they range through oceanic habitats. These growth rates can, therefore, be viewed as indicators of recent ocean productivity. Thus, our hypothesis was that estimated intra‐annual growth in body weight of immature and maturing age‐4 male and female chum salmon may be used as a biological indicator of variations in rearing conditions also experienced by age‐0 walleye pollock; consequently, they may be used to predict the recruitment to age‐1 in walleye pollock. Summer SST s and chum salmon growth at the end of July and September explained the largest amount of variability in walleye pollock recruitment indicating that physical and biological indices of ocean productivity can index fish recruitment.

Reassessing regime shifts in the North Pacific: incremental climate change and commercial fishing are necessary for explaining decadal‐scale biological variability - Michael A. Litzow; Franz J. Mueter; Alistair J. Hobday (Global Change Biology, 2014)
In areas of the North Pacific that are largely free of overfishing, climate regime shifts – abrupt changes in modes of low‐frequency climate variability – are seen as the dominant drivers of decadal‐scale ecological variability. We assessed the ability of leading modes of climate variability [Pacific Decadal Oscillation ( PDO ), North Pacific Gyre Oscillation ( NPGO ), Arctic Oscillation ( AO ), Pacific‐North American Pattern ( PNA ), North Pacific Index ( NPI ), El Niño‐Southern Oscillation ( ENSO )] to explain decadal‐scale (1965–2008) patterns of climatic and biological variability across two North Pacific ecosystems (Gulf of Alaska and Bering Sea). Our response variables were the first principle component ( PC1 ) of four regional climate parameters [sea surface temperature ( SST ), sea level pressure ( SLP ), freshwater input, ice cover], and PCs 1–2 of 36 biological time series [production or abundance for populations of salmon ( Oncorhynchus spp.), groundfish, herring ( Clupea pallasii ), shrimp, and jellyfish]. We found that the climate modes alone could not explain ecological variability in the study region. Both linear models (for climate PC 1) and generalized additive models (for biology PC 1–2) invoking only the climate modes produced residuals with significant temporal trends, indicating that the models failed to capture coherent patterns of ecological variability. However, when the residual climate trend and a time series of commercial fishery catches were used as additional candidate variables, resulting models of biology PC 1–2 satisfied assumptions of independent residuals and out‐performed models constructed from the climate modes alone in terms of predictive power. As measured by effect size and Akaike weights, the residual climate trend was the most important variable for explaining biology PC1 variability, and commercial catch the most important variable for biology PC2 . Patterns of climate sensitivity and exploitation history for taxa strongly associated with biology PC1–2 suggest plausible mechanistic explanations for these modeling results. Our findings suggest that, even in the absence of overfishing and in areas strongly influenced by internal climate variability, climate regime shift effects can only be understood in the context of other ecosystem perturbations.

Genetics, recruitment, and migration patterns of Arctic cisco (Coregonus autumnalis) in the Colville River, Alaska, and Mackenzie River, Canada - Christian E. Zimmerman; Andrew M. Ramey; Sara M. Turner; Franz J. Mueter; Stephen M. Murphy; Jennifer L. Nielsen (Polar Biology, 2013)

Spatial correlation patterns in coastal environmental variables and survival rates of salmon in the north‐east Pacific Ocean - Franz J. Mueter; Dan M. Ware; Randall M. Peterman (Fisheries Oceanography, 2002)
We examined spatial correlations for three coastal variables [upwelling index, sea surface temperature (SST), and sea surface salinity (SSS)] that might affect juvenile salmon ( Oncorhynchus spp.) during their early marine life. Observed correlation patterns in environmental variables were compared with those in survival rates of pink ( O. gorbuscha ), chum ( O. keta ), and sockeye ( O. nerka ) salmon stocks to help identify appropriate variables to include in models of salmon productivity. Both the upwelling index and coastal SST were characterized by strong positive correlations at short distances, which declined slowly with distance in the winter months, but much more rapidly in the summer. The SSS had much weaker and more variable correlations at all distances throughout the year. The distance at which stations were no longer correlated (spatial decorrelation scale) was largest for the upwelling index (> 1000 km), intermediate for SST (400–800 km in summer), and shortest for SSS (